Study of Modern Technologies of Sewing Manufacturing - D.A. Radjapova; S.A. Raximkulovа; I.B. Boltayeva; M.K. Urozov (Research Parks Publishing LLC, 2021)
The fashion direction for the classic style men's jacket is influenced by the world fashion direction, in which the prestige and position of men play an important role. But the fashion of this era is not entirely reversible. only certain modernized elements of the style of that period are applied. The same process is repeated in men's jackets.